From Potential To Development: Initial Exploring Warbal Village’s Marine Tourism Attractions - Francisca Titing Koerniawaty; I Made Trisna Semara; Sonctia Fanesia Renjaan (Institut Pariwisata dan Bisnis Internasional, 2026)
Warbal Village holds strategic potential as a community-based marine tourism destination, supported by its diverse marine resources and strong local community engagement, yet its development remains in an early stage. This study aims to analyze the destination life cycle position, potential, and challenges of marine tourism development in Warbal Village. A qualitative approach was employed using field observations, in-depth interviews, and documentation studies. Data were analyzed by integrating the Tourism Area Life Cycle (TALC) framework, the 4A concept, and the perspectives of Community-Based Tourism, Regenerative Tourism, Marketing 5.0, and the Pentahelix model. The findings indicate that Warbal Village is at the involvement stage, with key strengths in its natural coastal attractions and authentic local culture. However, limitations in accessibility, amenities, ancillary services, tourism management institutions, and digital promotion remain major challenges. The pristine coastal environment offers opportunities for the application of regenerative tourism, suggesting that destination development should be carried out gradually, in an integrated and collaborative manner to support tourism sustainability and local community well-being.